Impact of COVID 19 on Student Mobility in India - Khan, Tanuja; Thomas, Sheena (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
The Pandemic COVID 19 has left humanity stranded with a question ‘what next’. The student community is perplexed to make decisions on where to pursue their education from. The fear of contracting the disease along with many other associated challenges has altered decisions of many students. This paper examined the preferred destinations of Indian Students for graduation, factors affecting the decisions, the impact of gender on student mobility. The paper attempts to factor in all the major reasons which contribute in deciding where the students will be moving for their Higher Education Studies.